The effect of massage based on midnight-noon ebb-flow theory on the milk secretion of primiparas (子午流注循经按摩对初产妇乳汁分泌的影响) - QU Qinfang (屈勤芳); ZHANG Caixia (张彩霞); AN Rongrong (安溶溶); ZHOU Sufang (周素芳) (Association of Integrative Nursing, 2021)
Objective To explore the effect of massage based on midnight-noon ebb-flow theory on milk secretion primiparas. Methods A total of 70 primiparas were selected and divided into the control group and the study group, with 35 cases in each. Both groups were given breastfeeding for the first time within 2 hours, the control group was given regular massage, and the study group was given massage based on midnight-noon ebb-flow theory. The milk production, prolactin level, breast tenderness rating and breastfeeding rate were compared between the two groups. Results After 5 days of intervention, the levels of prolactin and milk production in the two groups increased compared with 24 hours postpartum, those in the study group were more than those in the control group, and the differences were statistically significant (P<0. 05). The rating of breast pain in the study group at 5 days postpartum was lower than that in the control group, the breastfeeding rate in the study group was higher than that in the control group, and the differences were statistically significant (74. 29% vs. 57. 14%, P<0. 05). Conclusion Massage based on the midnight-noon ebb-flow theory can further increase the milk secretion of primiparas, relieve the symptoms of breast tenderness, and increase the breastfeeding rate. (目的 探讨基于子午流注理论的循经按摩对初产妇乳汁分泌的影响。方法 选取2020年4月-2021年2月收治的初产妇70例, 随机分为对照组和研究组, 各35例。对照组给予常规循经按摩, 研究组实施基于子午流注理论的循经按摩。记录2组产后24 h和产后5 d的泌乳量和泌乳素水平, 观察2组产后5 d的乳房胀痛评级和母乳喂养率。结果 产后5 d, 2组泌乳素水平及泌乳量均较产后24 h增加, 且研究组优于对照组, 差异有统计学意义(P＜0. 05)。研究组乳房胀痛较对照组轻, 差异有统计学意义(P＜0. 05)。研究组产后5 d的母乳喂养率74. 29%, 高于对照组的57. 14%, 差异有统计学意义(P<0. 05)。结论 基于子午流注循经按摩可进一步提高初产妇乳汁分泌, 缓解乳房胀痛症状, 提高母乳喂养率。)